ROLE OF KUMARI SWARASA IN THE MARAN PROCESS OF SUDHA VARGA DRAVYAS WITH SPECIAL REFERANCE OF GODANTI BHASMA PREPARED BY TWO DIFFERENT METHODS - Deshmukh Kavita Shailesh (International Journal of Applied Ayurved Research, 2019)
In Rasashastra various herbal drugs are used for the Shodhan and Marana process of metals and minerals. Herbal drugs are used to purify,to reduce toxicity and to make it assimilate in the body. And mainly to convert inorganic metal and mineral into organic form.It is observed that for the Sudha varga dravyas Kumari swarasa(Aloe Vera Juice) is used for Shodhan and Marana process. To find out the role of Kumari in these processes research was done on Godanti bhasma. Godanti bhasma is prepared by two methods, one by giving only puta without bhavana and another method by giving bhavana of Kumari swarasa and then puta is given. Both the samples are analyzed with the help of ayurved and modern techniques like SEM,XRD and observations are compared. It is observed that the method in which Kumari swarasa is used percentage of Calcium is more.